CRITERIA FOR MENTAL HEALTH IN CHILDREN AND ITS MAINTENANCE - Djalolova Mohinur Abdusattor's daughter; Tashkoziyeva Dildora (Journals Park Publishing, 2023)
The article describes the criteria for ensuring children's health, the opinions of scientists, and the carried out program works.
Keywords: child, health, education, activity, necessity, stage, education, level, teacher, goal.